Potensi Pelaksanaan Self Monitoring Blood Glucose Pada Pasien Diabetes Dalam Meningkatkan Kualitas Hidup dan Kontrol Glikemik - Pandan Enggarwati; Debie Dahlia; Sri Yona (UIMA Press, 2020)
Abstract Introduction: Diseases that are considered particularly dominant in Indonesia are now starting to shift toward chronic diseases and one of which is diabetes mellitus (DM). Ever since a patient is diagnosed with DM, DM management must be carried out continuously and it will bring changes to the patients’ lifestyle. Health-Related Quality of Life (HRQoL) is a health indicator which covers interrelated subjective and multidimensional concepts, including assessment of physical, functional, psychological, and religious aspects. Self Monitoring Blood Glucose (SMBG) is a part of DM disease management which allows control of the glycemic index and quality of life. However, potential benefits of SMBG implementation needs to be discovered further. Objective: The purpose of this article is to determine the potential of SMBG in DM management and its relation to the glycemic index and quality of life. Methods: Literature review of this article based on EBSCOhost, PubMed, ProQuest, Willey Library Online dan ScienceDirect from 2013 - 2019. Results: The result shows that SMBG had a significant impact on HRQoL and glycemic index control. Conclusion: The role of nurses in the provision of comprehensive education is essential to increase the knowledge of the use of SMBG and drive patient’s motivation to ensure they are able to properly report the results of SMBG that they conducted.